2019
DOI: 10.1002/esp.4724
|View full text |Cite
|
Sign up to set email alerts
|

Submarine platform development by erosion of a Surtseyan cone at Capelinhos, Faial Island, Azores

Abstract: Erosion of volcanic islands ultimately creates shallow banks and guyots, but the ways in which erosion proceeds to create them over time and how the coastline retreat rate relates to wave conditions, rock mass strength and other factors are unclear. The Capelinhos volcano was formed in 1957/58 during a Surtseyan and partly effusive eruption that added an ~2.5 km2 tephra and lava promontory to the western end of Faial Island (Azores, central North Atlantic). Subsequent coastal and submarine erosion has reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Subaerial and submarine erosion rates can also be greatly enhanced when explosive volcanic eruptions emplace large volumes of easily erodible tephra. For example, Zhao et al (2019) documented very high erosion rates immediately after emplacement of the Capelinhos cone (Faial, Azores) that declined in inverse power-law fashion through later times. However, none of the cores in the central Aegean region shows a significant increase in sedimentation rate after the largest eruptions on Santorini, nor is such feature observed in the eastern cores after the Kos, Nisyros and Yali eruptions (Figure 9).…”
Section: Significance Of Sedimentation-rate Variationsmentioning
confidence: 99%
“…Subaerial and submarine erosion rates can also be greatly enhanced when explosive volcanic eruptions emplace large volumes of easily erodible tephra. For example, Zhao et al (2019) documented very high erosion rates immediately after emplacement of the Capelinhos cone (Faial, Azores) that declined in inverse power-law fashion through later times. However, none of the cores in the central Aegean region shows a significant increase in sedimentation rate after the largest eruptions on Santorini, nor is such feature observed in the eastern cores after the Kos, Nisyros and Yali eruptions (Figure 9).…”
Section: Significance Of Sedimentation-rate Variationsmentioning
confidence: 99%
“…The Azores Archipelago is frequently exposed to local wind‐waves and high‐energy swells generated by distant Atlantic storms (Carvalho, 2003; Rusu & Guedes Soares, 2012; Zhao et al ., 2019). Previous analysis of model outputs of the European Centre for Medium‐Range Weather Forecasts (ECMWF) showed that prevailing waves approach Santa Maria Island mainly from the north‐west (35%) and west (22%), with average significant wave heights of 2 m (Ricchi et al ., 2020).…”
Section: Regional Settingmentioning
confidence: 99%
“…Previous analysis of model outputs of the European Centre for Medium‐Range Weather Forecasts (ECMWF) showed that prevailing waves approach Santa Maria Island mainly from the north‐west (35%) and west (22%), with average significant wave heights of 2 m (Ricchi et al ., 2020). Waves are higher in winter than in summer (Zhao et al ., 2019). The North Atlantic Oscillation and Eastern Atlantic atmospheric circulation brings large storms (wave heights >16 m and peak periods >18 s) which affect the Azores Archipelago once every seven years on average (Andrade et al ., 2008; Quartau et al ., 2012; Zhao et al ., 2019; Ricchi et al ., 2020).…”
Section: Regional Settingmentioning
confidence: 99%
“…Extending temporal and spatial scales, we will be able to envisage morphologies like erosional continental shelves and volcanic insular shelves. The wave-base concept is of importance for modelling for continental shelves (Sunamura, 1978b;Trenhaile, 2001) and island shelves (Quartau et al, 2010(Quartau et al, , 2018Zao et al, 2019), and also for exploring the origin of submarine erosion surfaces (Rovere et al, 2011;Thom et al, 2010;Wilson & Luyendyk, 2006). Although multiple estimates of the wave base have been reported from many locations (Sunamura, 1992, table 6.2), almost all of them have not been based on sound field evidence.…”
Section: Introductionmentioning
confidence: 99%